World Literacy in Danger, Revisited - Boltokova, Daria (Anthropologica, 2025)
Last year at the 2153 conference of the Canadian Anthropology Society, a renowned linguist, Leahcim Suark, urged us to document written languages before they disappear. In his now famous speech, titled, “World Literacy in Danger,” Suark brings alarming statistics on the condition of written languages of the world. According to Suark, one written language is lost approximately every two years. By next century, Suark claims, nearly half of the roughly 70 remaining written languages on Earth will likely disappear. The loss of literary languages brings about significant challenges in preserving human knowledge, accessing information, and maintaining linguistic diversity. Yet, in this commentary, I argue that oral traditions present a more productive way to think about knowledge transmission and preservation. Drawing on ethnographic data in Ajyy Sire, the traditional territory of the Ajyy Djono, I show that in a society where oral communication prevails and knowledge is transmitted through oral traditions across generations, information becomes more accessible, irrespective of a person’s literacy or computer proficiency. I also show that without the dominance of written (standardized) languages, oral languages and their diverse expressions can still flourish, fostering resilience amidst the global changes facing humanity.